Gold nanoshells with varying morphologies through templated surfactant‐assisted seed‐growth method - Lee, Sunghee; Lee, Soyun; Hwang, Soojin; Park, So‐Jung (Bulletin of the Korean Chemical Society, 2024)
Plasmonic nanoparticles exhibit dramatic changes in optical properties depending on their spatial organization. Therefore, the ability to precisely control their assembly structure is important for both fundamental understanding and practical applications. In this personal account, we describe a templated surfactant‐assisted seed‐growth method to synthesize core–shell‐type gold nanoparticle assemblies with controllable surface morphologies and optical properties. This approach provides a simple procedure for simultaneous growth and assembly of metal nanoparticles on polymer templates, producing well‐defined nanostructures such as spiky nanoshells and raspberry‐like metamolecules with useful and interesting optical properties, such as strong and uniform surface‐enhanced Raman scattering and metamaterial properties. We discuss the factors that control the morphology and collective properties, describe the design rules acquired from the system, and suggest future directions of this research area. The synthetic approach reviewed in this paper offers an alternative strategy to typical self‐assembly methods for controlled assembly of metal nanoparticles. This method, based on templated seed‐mediated metal growth, produces various types of metal nanoshells such as continuous or spiky nanoshells, as well as raspberry‐like metamolecules with unique optical properties, including strong and distance‐independent SERS, heterogeneity‐driven quadrupole‐enhanced SERS, and strong magnetic resonances with broad extinction spectra. This account discusses the factors that control the morphology and optical properties and suggests future directions in this field.